Indeks Harary Pada Graf Koprima Pada Grup Bilangan Bulat Modulo Berorde Pangkat Prima - Udayana Devandra (Universitas Nusa Cendana, 2023)
The coprime graph in modulo integer groups has many important applications in discrete mathematics and cryptography. The Harary index of the coprime graph is very useful in many mathematical and computer science applications, especially in computing algebraic properties, topology, and graph structure. In this article, the Harary index of the coprime graph for modulo integer groups with a prime power order was obtained, which is the square of the sum of the group members minus one.